New research for the distortion of steel box girders with inner solid diaphragms. Issue 14 (October 2019) - Ren, Yangzhi; Wang, Bin; Li, Yinqi; Liu, Xuechun
Toward estimating accurately the distortional response of box girders, in this article, distortion of steel box girders strengthened with intermediate solid diaphragms under eccentric loads is analyzed by employing the so-called initial parameter method. A new model of high-order statically indeterminate structure was established with three orthogonal redundant forces acting at the junction between the girder and diaphragms. Emphasis is put onto the interaction between the girder and diaphragms, where a hypothetical bi-moment B pi indicating all longitudinal redundant force components for diaphragm was proposed besides the moment Mpi for in-plane shear component. Simplified initial parameter method solutions for distortional angle and distortional warping stresses and displacements were derived based on the in-plane and out-of-plane compatibilities between the girder and diaphragms. Taking box girders with three and five intermediate diaphragms as an example, the proposed initial parameter method solutions have good agreement with the finite element analysis ones. Finally, distortional behavior under moving eccentric loads is investigated, resulting in a bowl-shaped curve for moment Mpi and an approximate trigonometric function for bi-moment Bpi . Results show that diaphragms have a stronger resistance on in-plane distortional shear for the loads in midspan than on ends. Plus, the thick diaphragm holds a stronger restraint on distortional warping deformations and stresses than the thin one.